Abundance and richness of the subfamily Cryptinae (Hymenoptera: Ichneumonidae) in a tropical forest of Panama (UNED Research Journal, 2025)
Introduction: Cryptinae is the most diverse and abundant subfamily within the Ichneumonidae. However, its study in Panama has focused on a limited number of species, hindering the understanding of its population dynamics in the region. Objective: To evaluate the abundance and species richness of Cryptinae wasps in a tropical forest of Panama. Methods: I analyzed 2 080 Ichneumonidae (Cryptinae) samples from Malaise traps on Barro Colorado Island, Panama, from the period 2014–2017. Results: Cryptinae were abundant but low in species richness, likely due to the island’s low elevation. Abundance was higher during the dry season and declined strongly in wetter years. Conclusion: Cryptinae is the most abundant Ichneumonidae subfamily in the island, with population patterns shaped by seasonal and climatic factors, particularly temperature and precipitation.
Keywords: wasps; parasitoids; seasonality; Hymenoptera; biological regulators; climate change